Oxidation-Specific Epitopes in Non-Alcoholic Fatty Liver Disease - Hendrikx, Tim; Binder, Christoph J. (Frontiers in Endocrinology, 2020)
An improper balance between the production and emission of intracellular reactive oxygen species causes increased oxidative stress. Consequently, DNA, RNA, proteins and lipids are irreversibly damaged, leading to molecular modifications that disrupt normal function. In particular, the peroxidation of lipids in membranes or lipoproteins alters lipid function and promotes neo-epitope formation, so-called oxidation-specific epitopes (OSEs), which are found to be present on (lipo)proteins, dying cells and extracellular vesicles. Accumulation of OSEs and recognition of OSEs by designated pattern recognition receptors on immune cells or soluble effectors can contribute to the development of chronic inflammatory diseases. In line, recent studies highlight the involvement of modified lipids and OSEs in different stages of the spectrum of non-alcoholic fatty liver disease (NAFLD), including inflammatory non-alcoholic steatohepatitis (NASH), fibrosis and hepatocellular carcinoma. Targeting lipid peroxidation products shows high potential in the search for novel, better therapeutic strategies for NASH.